Diseño del plan de prevención, preparación y respuesta ante emergencias para la fundación Liborio Mejía sede Neiva - Cano Trujillo, Laura Alejandra (Universidad Antonio Nariño, 2021)
This document was developed at the Liborio Mejía Foundation, it is a non-profit entity, with the objective of promoting peace, coexistence, access to justice and the participation of Colombians, in order to contribute to the construction of a company capable of resolving and managing conflicts in a peaceful, direct and negotiated manner, at the Neiva headquarters there are 4 employees, two legal assistants, a lawyer and the manager, this headquarters does not have a prevention, preparation and response plan for emergencies and this makes the Foundation in a vulnerable situation to a series of risks that can affect daily activities, these events can cause emergencies which can generate serious injuries, material damage, environmental impacts that are caused by natural hazards, anthropic and social, such as fires, floods, earthquakes, explosions, electrical failures in equipment and theft. for which the main priority is the design of the plan for prevention, preparation and attention to emergencies.